Economic aspects of social services development in Slovakia in the context of demographic changes - Gavurová, Beáta; Šoltés, Michal (Univerzita Pardubice, 2016)
At present, the global aging process of inhabitants represents a serious social challenge that is related to those countries whose size or economic power is not that significant aspect. Rapid increase of older population results in an increasing inquiry of long-term health care services (long-term care – LTC). As a result of a progress in research as well as investments in health care services, health care constantly improves, but there are increasing inequalities in health of vulnerable groups of inhabitants, such as elderly. The given article focuses on the above mentioned facts and its primary aim is to emphasize the importance of multi-dimensional analyses of available social services in the process of population global aging. In the presented partial results, the research focused on the analysis of social services providers in Slovakia from the point of view of their form, structure, capacity and regional differences. The secondary aim of the article is concentrated on an urgent need to resolve the issue of the Slovak population aging by means of chosen demographic indicators, as well as it focuses on a significance of legal framework formation that would provide long-term health care in Slovakia via social and health care services development.
Keywords: ageing population; social system; health system; social service providers; long-term care; I10; I15; I18